Mandatory dividend rules: Do they make it harder for firms to invest? - Martins, Theo Cotrim; Novaes, Walter (Journal of Corporate Finance, 2012)
What are the costs and benefits of mandatory dividend rules? On the one hand, they make it harder for controlling shareholders to divert corporate assets. On the other hand, they reduce the internal funds available for firms to invest, possibly leading to the loss of valuable projects. To assess this trade-off, we look at investment and dividend decisions in a sample of public firms in Brazil. We show that a significant fraction of these firms use loopholes of Brazil's mandatory dividend rules to avoid paying dividends. And yet, the dividend rules are effective. They help explain why the average dividend yield in Brazil is higher than in the U.S., without making it harder for firms to invest.